Phenolic compounds in grapes and wines: Chemical and biochemical characteristics and technological quality - Vanzela, Ellen Silva Lago [UNESP]; Baffi, Milla Alves; De Castilhos, Maurício Bonatto Machado [UNESP]; Pinto, Marcos Roberto Moacir Ribeiro; Bianchi, Vanildo Luiz Del [UNESP]; Ramos, Afonso Mota; Stringheta, Paulo César; Hermosín-Gutiérrez, Isidro; Da-Silva, Roberto [UNESP] (My University, 2014)
The grape is one of the most widely consumed fruits in the world, both in natural and in processed forms and the economic importance generated by the sale of this products is notorious. It is considered one of the greatest sources of phenolic compounds when compared to other fruits and vegetables, but there is a great diversity among cultivars resulting in grapes with different characteristics, which is directly linked to its polyphenol profile. The phenolic compounds are secondary metabolites of plants, playing important physiological activities, and their concentration is subjected to great variation. They can be classified into two groups: non-flavonoids and flavonoid. In the grape, the nonflavonoids are mainly phenolic acids and the stilbenes and flavonoids are anthocyanins, flavonols and flavan-3-ols (monomers, dimers, oligomers and polymers, the latter also known as tannins). Epidemiological, clinical and in vitro studies have demonstrated some of the biological effects associated with dietary phenolic compounds such as antioxidant, anti-inflammatory, antimicrobial and anti-carcinogenic activities. In grapes and their products, phenolic compounds are directly related to sensory characteristics such as color and flavor. However, grape juices and, mainly, red wines present phenolic composition more complex than that which is found in the grapes used for their preparation. The qualitative and quantitative differences are largely due to numerous chemical and biochemical oxidative processes. These oxidative processes may lead to changes in the color and the nutritional value of grapes and its products. In contrast, the deliberate addition of specific enzyme preparations in key stages in the manufacturing process plays a crucial role in improving the quality of products such as juices and, especially, wines. This is because the grape skins are limiting barriers that prevent the release of phenolics to the must. The extraction of these compounds during the maceration requires that the middle lamella and cell walls are broken to allow the extraction of constituents present within the cell vacuoles. Furthermore, wines usually need to be stabilized to get rid of unstable compounds such as potassium bitartrate. That's why this chapter summarizes the current knowledge on the chemical characteristics of phenolic compounds in grapes and their products and highlights some aspects related to their impact on color, flavour and health properties, with examples taken mostly from research on grapes and wine. Furthermore, presents a discussion of the state of the art of the main natural and induced biochemical processes that occur in the grape during processing which can positively or negatively affect the phenolic compounds and, hence, the sensory and nutritional quality of any derived products.
Keywords: Enzyme; Grape; Oxidative processes; Phenolic compounds; Wine